The effectiveness of a psychoeducation intervention delivered via WhatsApp for mothers of children with autism spectrum disorder (ASD) in the Kingdom of Saudi Arabia: a randomized controlled trial - Hemdi, A.; Daley, David (Wiley, 2017)
Background